Second Metatarsophalangeal Joint Interpositional Arthroplasty Using Decellularized Human Dermal Allograft. Issue 4 (16th October 2019) - Bohl, Daniel D.; Idarraga, Alex J.; Hur, Edward S.; Lee, Simon; Hamid, Kamran S.; Lin, Johnny
Category: Lesser Toes Introduction/Purpose: Success has been reported in treating first metatarsophalangeal joint osteoarthritis with allograft interpositional arthroplasty, but little has been published regarding the use of similar techniques for the second metatarsophalangeal joint. We hypothesized that second metatarsophalangeal joint allograft interpositional arthroplasty would result in improvement in patient-reported outcomes, a low rate of postoperative complications, and a low rate of reoperation at minimum follow-up of one year. Methods: A retrospective review of medical records was conducted for patients having undergone allograft interpositional arthroplasty of the second metatarsophalangeal joint with at least one year of postoperative follow-up. Our technique included a dorsal incision and joint exposure, removal of the cartilage from the metatarsal head using a conical reamer, suture of a human decellularized dermal allograft to the metatarsal head though drill holes, and capsular repair (Figure 1). Preoperative and postoperative findings were compared, including Foot Function Index (FFI) and radiographic joint space measured on the AP view. Postoperative range of motion and satisfaction with the procedure were quantified. Results: In total, 5 patients met inclusion criteria. Mean follow-up was 3.2+/-2.1 years. Three of 5 patients (60.0%) reported that they would have the procedure again, and mean satisfaction with the procedure was 6.0+/-5.1 out of 10. One patient had conversion to fusion at 2 postoperative years. Among the 4 unfused patients, Foot Function Index decreased from 75.7+/-29.8 preoperatively to 52.0+/-46.5 at final follow-up (p=0.526). Mean final arc of motion was 35.0+/-7.1 degrees. Radiographic joint space was 0.4+/-0.3 mm preoperatively, increased to 2.2+/-0.5 mm immediately postoperatively, and decreased to 1.5+/-0.8 mm at final follow-up. The final follow-up joint space trended towards a larger number among the patients who stated they would have the procedure again compared to the patients who stated they would not (2.6+/-1.0 mm versus 0.4+/-0.4 mm, p=0.178). Conclusion: Second metatarsophalangeal joint allograft interpositional arthroplasty is a reasonable alternative to arthrodesis for management of isolated late-stage second metatarsophalangeal joint osteoarthritis. Arthrodesis of the second metatarsophalangeal joint is suboptimal due to altered gait mechanics; hence, novel joint preserving procedures are of value. Despite the modest results of interpositional arthroplasty in this limited series, the procedure can result in pain relief while allowing for motion in a subset of patients. The major determinant of success among our cohort was the maintenance of radiographic joint space at final follow-up.